The vitamin D receptor Taq I polymorphism is associated with reduced VDR and increased PDIA3 protein levels in human intestinal fibroblasts - Gisbert-Ferrándiz, Laura; Cosin-Roger, Jesus; Hernández, Carlos; Macias-Ceja, Dulce C.; Ortiz-Masiá, Dolores; Salvador, Pedro; Wildenberg, ME; Esplugues, Juan V.; Alós, Rafael; Navarro, Francisco; Calatayud, Sara; Barrachina, María D. (The Journal of steroid biochemistry and molecular biology, 2020)
The synonymous single nucleotide polymorphism (SNP) rs731236, located in the vitamin D receptor (VDR) gene (Taq I) has been associated with both decreased levels of the protein in peripheral blood mononuclear cells and a fibrosis-related complication in Crohn´s disease (CD). Interactions between VDR and a protein-disulfide isomerase-associated 3 (PDIA3) in the regulation of extracellular matrix have been reported and we aim to analyze the relevance of the VDR genotypes and the effects of Vitamin D (VD) in the expression of VDR, PDIA3 and proliferation of intestinal fibroblasts. Human intestinal fibroblasts were isolated from the non-affected surgical resections of colorectal patients and classified according to the VDR genotype. In some cases, cells were transfected with specific PDIA3 siRNA. Basal and VD-stimulated expression of VDR, PDIA3 and Collagen 1A1 (COL1A1) as well as fibroblast migration/proliferation were analyzed. Our data show that intestinal fibroblasts homozygous for the C allele in the VDR gene exhibited lower VDR protein levels and higher proliferation than cells homozygous for the T allele. VD increased VDR and attenuated the accelerated proliferation of CC fibroblasts. The diminished VDR level detected in CC cells was associated with increased levels of both PDIA3 and COL1A1 expression and the transient silencing of PDIA3 significantly reduced COL1A1 expression. We conclude that intestinal fibroblasts homozygous for the C allele in the VDR gene exhibited: reduced VDR protein levels, increased proliferation and increased PDIA3/COL1A1 expression. Treatment with VD increased VDR and attenuated proliferation of these cells.